Rescue of retinal ganglion cells in optic nerve injury using cell-selective AAV mediated delivery of SIRT1 - Ross, Ahmara G. (Gene Ther, 2021)
SIRT1 prevents retinal ganglion cell (RGC) loss in models of optic neuropathy following pharmacologic activation or genetic overexpression. The exact mechanism of loss is not known, prior evidence suggests this is through oxidative stress to either neighboring cells or RGC specifically. We investigated the neuroprotective potential of RGC-selective SIRT1 gene therapy in the optic nerve crush (ONC) model. We hypothesized that AAV-mediated overexpression of SIRT1 in RGCs reduces RGC loss, thereby preserving visual function. Cohorts of C57Bl/6J mice received intravitreal injection of experimental or control AAVs using either a ganglion cell promoter or a constitutive promoter and ONC was performed. Visual function was examined by optokinetic response (OKR) for 7 days following ONC. Retina and optic nerves were harvested to investigate RGC survival by immunolabeling. The AAV7m8-SNCG.SIRT1 vector showed 44% transduction efficiency for RGCs compared with 25% (P > 0.05) by AAV2-CAG.SIRT1, and AAV7m8-SNCG.SIRT1 drives expression selectively in RGCs in vivo. Animals modeling ONC demonstrated reduced visual acuity compared to controls. Intravitreal delivery of AAV7m8-SNCG.SIRT1 mediated significant preservation of the OKR and RGC survival compared to AAV7m8-SNCG.eGFP controls, an effect not seen with the AAV2 vector. RGC-selective expression of SIRT1 offers a targeted therapy for an animal model with significant ganglion cell loss. Over-expression of SIRT1 through AAV-mediated gene transduction suggests a RGC selective component of neuro-protection using the ONC model. This study expands our understanding of SIRT1 mediated neuroprotection in the context of compressive or traumatic optic neuropathy, making it a strong therapeutic candidate for testing in all optic neuropathies.